Ciril-Metodiana 19. in 20. stoletja - Orožen, Martina (Edinost in dialog, 2013)
Cyrill-Metodiana of the 19th and 20th century At this year's 1150th anniversary of arrival of the holy brothers to Moravia (863) this contribution seeks to outline the three stages of development of the Cyrillo-Metodiana in the Slovenian region. Firstly, the paper indicates the revival of their adoration in the 19th century in the Slovenian territory. It has been watery and both in the religious as well as in the linguistic and ethnic context extremely marked. This was contributed by scientific discoveries of the oldest linguistic monuments from the time of Christianization (Freising Monuments and the Old Church Slavonic literature) - and connection to the religious and cultural life in Moravia in the common country Austria. However, with the difference that the memory there of the holy brothers originates from their actual presence in ancient times. In the 20th century in the changed political frameworks (the formation of Yugoslavia and Czechoslovakia) the view of the linguistic issues diverts towards the religious content of the messages and the translation of Žitije in individual Slavic languages, including Slovenian (Fr. Grivec, 1936, 1951). Thanks to the culturally-minded theologians (Prof. of Faculty of Theology Fr. Grivec, A.C. Stojan, Archbishop Olomouc) the factual effort for religious and theological understanding, learning is revived, and on this basis the long-term convergence with the Orthodox world of the Southern east Europe. The Velehrad Academy is established and organized international meetings of theologians at seven Velehrad congresses (1907 - 1936). These are preparing the basis for the development of contemporary ecumenism. After the Second World War the unfavourable political and social situations in Slovenia stop the presence of Cyrillo-Metodiana in public. It is withdrawn in the scientific and theological "privacy". It is present externally only along the construction of churches dedicated to St. Cyril and Methodius. This reticence in public is still very typical for Slovenia while each anniversary (i.e. 1963, 1985, 20150) in the Czech Republic and Slovakia is within the political frameworks being increasingly commemorated in journalism, science, culture and religious life of the Church.
Keywords: Cyrillus, svetnik, 826-869; Methodius, svetnik, 815-885; Christianity; krščanstvo; svetniki; češčenje; Slovenia; Slovenija; Slovaška; Češka; Czech Republic